1993
DOI: 10.1029/93jd01225
|View full text |Cite
|
Sign up to set email alerts
|

Structure and seasonal variability of the nighttime mesospheric Fe layer at midlatitudes

Abstract: Lidar measurements of mesospheric Fe were conducted for 325 h during 75 nights at Urbana, Ill. (40°N, 88°W), in fall 1989 and from spring 1991 through summer 1992. The Fe layer abundance and root‐mean‐square (RMS) width have strong annual variations, with minima in summer. The abundance varied from 3.5 × 109 to 25 × 109 cm−2 with a mean of 10.6 × 109 cm−2, and the RMS width varied from 2.3 to 5.3 km with a mean of 3.4 km. The centroid height of the Fe layer has a strong semiannual variation, with minima at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
124
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 36 publications
12
124
4
Order By: Relevance
“…In addition, the Na layer always shows a few kilometers more extension on its top side than the Fe layer. These features can be seen also from a comparison of simultaneously observed Na and Fe layers at high, mid, and low latitudes respectively (Kane and Gardner, 1993;Lynch et al, 2005;Shibata et al, 2006), which may be universal. They provide a connection between the two different metallic species in the mesopause region.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, the Na layer always shows a few kilometers more extension on its top side than the Fe layer. These features can be seen also from a comparison of simultaneously observed Na and Fe layers at high, mid, and low latitudes respectively (Kane and Gardner, 1993;Lynch et al, 2005;Shibata et al, 2006), which may be universal. They provide a connection between the two different metallic species in the mesopause region.…”
Section: Introductionmentioning
confidence: 78%
“…This is consistent with the fact that Fe is the main component of the meteoric source, whereas the alkali metals are the minor ones (Heide and Wlotzka, 1995). Among the alkali metals, only the Na layer has a typical abundance value approaching that of the Fe layer (Kane and Gardner, 1993;Gardner et al, 2005;Yi et al, 2009). Hence a detailed quantitative comparison between the Na and Fe layers at a given site is feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found an average of 6.2% occurrence of strong Na s , although cited as much higher than observed at other mid-latitude locations. Kane and Gardner (1993) report on a total Fe s occurrence rate of 27% for the site of Urbana, Illinois (40 • N, 88 • W). In spite of this, the Ca s rate at Kühlungsborn, Germany was found to be 43% in annual mean.…”
Section: Discussion Of the Observationsmentioning
confidence: 99%
“…The peak Fe density, occurring around 85 km, is some 1.5 x 10 4 cm -3 at maximum [Kane and Gardner, 1993] compared to a total density at this altitude of some 10 TM cm -3 [Hedin, 1991]. The total density of ionized metal, on the other hand, is observed to be perhaps only an order of magnitude or so less dense than the total ionosphere [e.g., Kopp, 1997] in the region where the metal layers predominate, around 95 km.…”
Section: Introductionmentioning
confidence: 99%